Modelagem agro-hidrológica: abordagens recentes e aplicação de modelo em latossolo - Oliveira, Vinícius Henrique Dias de (2024)
Agro-hydrological modeling is a fundamental tool for simulating water movement in the soil and understanding the interaction of pesticides with the soil-plant-wateratmosphere system. The first part of this work reviews recent research, addressing pesticide use, associated risks, modeling methodologies, their limitations, challenges, and future perspectives. Agro-hydrological modeling aids researchers and farmers in understanding the effects of management practices on the environment, particularly regarding climate change and land use. These tools are essential for developing sustainable agricultural strategies that minimize environmental impacts and optimize production. Additionally, they contribute to the formulation of public policies aimed at protecting water and soil resources. The future of modeling includes the use of emerging technologies, such as remote sensing and real-time data, increasing precision and efficiency in the sustainable management of agricultural ecosystems. Regarding the prediction of pesticide movement in the soil, particularly in groundwater, mathematical models are calibrated using experimental data to understand the dynamics of these compounds. The second part of this study evaluated the capacity of the MACRO 5.2 model to describe water movement and atrazine distribution in a cornfield in western Paraná, using data from a lysimeter under simulated high-intensity rainfall. The model was adjusted by considering water percolation and pesticide levels in the percolate. After adjustments to the hydrological parameters, atrazine concentrations were calibrated with slight changes in sorption and degradation rates. The results, statistically evaluated, showed an estimate of 0.71%, 4.63%, and 3.05% of the total mass of atrazine in the percolate, surface runoff, and retention in the soil, respectively, confirming the model's adequacy in predicting atrazine transport.